STUDY ON WASTE MANAGEMENT THROUGH SEPARATION INCREASING THE INCOME OF NEW DITCH PURING MARKET MANAGERS: Universitas Nahdlatul Ulama Kalimantan Barat - Joni, Herkulanus (Jurnal Teknologi Infrastruktur, 2022)
ABSTRACT Waste is material that is disposed of from sources of human activity and natural processes that do not yet have economic value. This study aims to determine the level of waste generation at the Melati Puring Market and determine the percentage of waste generation transported to the TPA (Final Processing Site) after waste segregation. This study used 10 samples of market traders with an implementation time of 8 days. Measurement of waste samples is done by calculating the weight of waste per kg and per liter. The measurement method in this study used SNI 19-3964-1994. The method for taking and measuring samples of urban solid waste generation and composition. Data analysis using quantitative data analysis. The measurement of waste generation at the Melati Puring Market shows quite large results with a total waste generation of the entire shop of 418.75 kg/day. Separation of waste composition with total waste generation from 10 samples was 297.2 kg, the total average was 37.2 kg/day and the average waste generation per shop was 3.27 kg/day. The largest percentage of waste generation is organic waste which reaches 74% and the smallest percentage of waste generation is metal, rubber and cloth/textile waste which reaches 1%. Waste transported to TPA (Final Processing Site) can be reduced by 85% and the remaining only 15% (4% wood, 1% cloth/textile, 3% glass/glass, 1% rubber and 6% other waste) of the total waste generation from the Melati Puring Market. The total generated waste that is sorted can increase the income of market managers with an estimated profit of IDR 580,454 to IDR 617,846 in 1 week. Keywords: Puring Melati Market, Waste Management, Final Processing Site, Waste Generation.